(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The crisis in the Ukrainian countryside and agriculture, which has been going on for years, causes a particular need to find ways to solve it. Balanced development of rural areas can occur mainly due to changes in the rural economy and taking a course to develop the service sector in villages and create new jobs. The condition for improvement is the self-organization of rural territorial communities to find the possibility of using available resources. As for rural areas, there are many ideas, programs, and projects to support ecological and socio-economic growth at the local scale. The article highlights the social, ecological, and economic aspects that characterize the development of rural areas in recent years and proposes ways of balanced development of rural areas based on the use of modern methods in the interaction of administrative, organizational, and legal support. The rural areas of Ukraine have powerful natural, human, production, and social potentials that can ensure competitive production, stable economic growth, and a high standard of living for the rural population. Balanced development of rural areas and solving the problems of the rural population are among the main conditions for the democratic development of society and its economic and social well-being. Therefore, it should become a priority direction of the development of our state.